Dysregulation of dopamine receptor D2 as a sensitive measure for Huntington disease pathology in model mice - Crook, Zachary R. (National Academy of Sciences, 2012)
The ability to quantitatively evaluate the impact of a potential therapeutic intervention for Huntington disease (HD) in animal models for the disease is a critical step in the pathway to development of an effective therapy for this devastating neurodegenerative disorder. We report here an approach that combines a cell-based assay’s quantitative accuracy and direct relationship to molecular processes with the ability to directly monitor effects in HD model mouse neurons. To accomplish this goal, we have developed an accurate quantitative reporter assay for a transcript known to be down-regulated as an early consequence of mutant huntingtin expression. This system uses mouse strains carrying a GFP reporter for the expression of the dopamine receptor D2, expressed in the medium spiny neurons of the basal ganglion. This receptor consistently demonstrates reduced expression in patients and murine models, and the FACS-based assay gives a highly accurate and quantitative readout of this pathology in mouse neurons expressing mutant huntingtin. For four genetic models and one viral model, a highly reproducible time course of loss of reporter expression is observed. This quantitative measure of HD pathology can be used to measure the effects of HD therapeutics in small cohorts with high confidence. We further demonstrate that the introduction of an shRNA against the huntingtin transgene by virus can improve this pathological status in medium spiny neurons transduced with the construct. We believe this system can be of great utility in the validation of effective therapeutic interventions for HD.